Enhancing D-lactic acid production from non-detoxified corn stover hydrolysate via innovative F127-IEA hydrogel-mediated immobilization of Lactobacillus bulgaricus T15 - Zheng, Yuhan; Sun, Feiyang; Liu, Siyi; Wang, Gang; Chen, Huan; Guo, Yongxin; Wang, Xiufeng; Escobar Bonora, Maia Lia; Zhang, Sitong; Li, Yanli; Chen, Guang (Frontiers in Microbiology, 2024)
BackgroundThe production of D-lactic acid (D-LA) from non-detoxified corn stover hydrolysate is hindered by substrate-mediated inhibition and low cell utilization times. In this study, we developed a novel temperature-sensitive hydrogel, F127-IEA, for efficient D-LA production using a cell-recycle batch fermentation process.ResultsF127-IEA exhibited a porous structure with an average pore size of approximately 1 μm, facilitating the formation of stable Lactobacillus bulgaricus clusters within the gel matrix. It also maintains excellent mechanical properties. It also maintains excellent mechanical properties. F127-IEA immobilized Lactobacillus bulgaricus T15 (F127-IEA-T15) can be used in cell-recycle fermentation for over 150 days from glucose and 50 days from corn stover hydrolysate, achieving high production rates of D-LA from glucose (2.71 ± 0.85 g/L h) and corn stover hydrolysate (1.29 ± 0.39 g/L h). F127-IEA-T15 enhanced D-LA production by adsorbing and blocking toxic substances present in corn stover hydrolysate that are detrimental to cellular activity.ConclusionsThe newly developed hydrogels in this study provide a robust platform for large-scale extraction of D-LA from non-detoxified corn stover.